The Multilateral Donor Non-System: Towards Accountability and Efficient Role Assignment - Helmut Reisen (Kiel Institute for the World Economy (IfW), 2009)
Global governance refers to several pillars; one important pillar is the multilateral aid architecture. Its reform can be discussed under the perspectives of representativeness, inclusiveness, and efficiency (of aid delivery).A prerequisite for efficient aid delivery is to map the rising complexity of multilateral development finance, to help identify areas for consolidation, address fragmentation and poor co-ordination at country level, and help identify comparative advantages for an institutional role assignment among multilateral agencies. After doing just that, the paper explores why the multilateral donors have proliferated and provides broad recommendations for a more efficient and accountable multilateral donor system.
Keywords: F35; O19; 330; Foreign aid; international organizations; Entwicklungshilfe; Entwicklungskooperation; Entwicklungsorganisation; Global Governance; Internationale wirtschaftspolitische Koordination; Welt; Entwicklungsländer